Descemet's membrane endothelial keratoplasty: surgical outcomes and endothelial cell count modelling from a UK centre. (October 2018) - Fajgenbaum, Mark; Kopsachilis, Nick; Hollick, Emma
Abstract Purpose To report surgical outcomes and endothelial cell density (ECD) trends up to 2 years post-operatively in the first cohort of eyes undergoing Descemet's membrane endothelial keratoplasty (DMEK) for low-to-moderate risk indications at our UK centre. Tight corneal sutures were used to ensure high intraoperative pressure from intracameral air for 10-min and to maintain a good post-operative air fill. Outcomes were compared to a prior series at our unit of similar eyes having Descemet's stripping endothelial keratoplasty (DSEK). Methods Retrospective, interventional series. Inclusions: all DMEKs with a minimum of 1-month follow-up. Exclusions: prior glaucoma surgery, penetrating keratoplasty or anterior chamber lens. Results 88 DMEKs met inclusion. Median follow-up: 332 days. Main indication: Fuchs dystrophy (90%). Complications: re-bubbling 2%, primary failure 6%, retinal detachment 2%, rejection 3%. At 3 months, BCVA ≥6/6 and ≥6/9 were 67% and 86%, respectively. Graft survival at both 1 and 2 years was 94 ± 2%. Mean(±SD) cell-loss at 1 month, 3 months, 6 months, 12 months and 24 months: 30 ± 15%, 29 ± 16%, 33 ± 17%, 35 ± 17% and 48 ± 16%, respectively. Compared to a prior series at our unit of 210 low-to-moderate risk DSEKs, cell loss was lower for DMEK at all time-points (p < 0.001) through to 12 months but was not statistically different at 24 months. Mixed-modelling of ECD over time demonstrated the convergence of DMEK and DSEK curves by 2 years. Conclusions DMEK using tissue from UK eye-banks resulted in high survival and excellent visual acuity. ECD through 1 year was superior to DSEK in a similar cohort. Our low re-bubble rate (2%) may be attributable to use of intracameral air at temporarily elevated intraocular pressure.